Hugo Zapałowicz’s species of Iris and Gladiolus (Iridaceae): Typification of his names - Zhygalova, Svitlana Leonidovna; Olshanskyi, Igor Grygorovych (Phytotaxa, 2014)
Iridaceae Jussieu (1789: 57) includes more than 60 genera and about 800 species (Goldblatt & Manning 2008) widely distributed in tropical, subtropical, and temperate regions, and especially numerous in Africa south of the Sahara, the eastern Mediterranean, western and eastern Asia, and Central and South America (Takhtajan 2009). Ten genera and about 100 species occur in Europe, some of which were described from  Europe. We have reviewed the Herbarium of the Władysław Szafer Institute of Botany PAS (KRAM). Consequently, we here lectotypify two Iridaceae taxa described by H. Zapałowicz.